2018
DOI: 10.3390/rs10010081
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of a Fluorescent Dye in a Freshwater Lake with an Unmanned Surface Vehicle and an Unmanned Aircraft System

Abstract: Recent catastrophic events in our oceans, including the spill of toxic oil from the explosion of the Deepwater Horizon drilling rig and the rapid dispersion of radioactive particulates from the meltdown of the Fukushima Daiichi nuclear plant, underscore the need for new tools and technologies to rapidly respond to hazardous agents. Our understanding of the movement and aerosolization of hazardous agents from natural aquatic systems can be expanded upon and used in prevention and tracking. New technologies with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…These results suggest that reliable inference of dye concentrations from remotely sensed data might be contingent upon the background optical characteristics of the water body. Powers et al [9] also showed that image data acquired from a small unoccupied aircraft system (sUAS) could be used to map another type of visible dye, called fluorescin, following its injection into a small reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that reliable inference of dye concentrations from remotely sensed data might be contingent upon the background optical characteristics of the water body. Powers et al [9] also showed that image data acquired from a small unoccupied aircraft system (sUAS) could be used to map another type of visible dye, called fluorescin, following its injection into a small reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…Aerosolized droplets may be produced in several ways, including bubble-bursting and fragmentation from breaking waves (Wu, 1981 ). Fluorescent dyes have been released as surrogate pathogenic microorganisms, and tracked with teams of unmanned systems in the water and in the air (Powers et al, 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, UAV and USV platforms can both collect imagery in addition to acoustics to improve estuarine mapping when compared with UAV imagery alone (Mancini, Frontoni, Zingaretti, & Longhi, ), although both methods are limited by vegetation shadowing. Powers, Hanlon, and Schmale () performed USV tracking of a tracer dye “pollutant” from UAV imagery, demonstrating the power of real‐time combined datasets, which may improve sampling and data acquisition, especially in unknown or difficult to observe environments.…”
Section: The State Of the Artmentioning
confidence: 99%
“…USV deployment in fluvial environments ranges from topographic to biophysical data collection (Casper, Steimle, Hall, & Dixon, ; Mancini et al, ; Suhari & Gunawan, ; Wei & Zhang, ; Young et al, ). The majority of these systems focus on bathymetric data collection from echo sounders, yet there are examples of both camera and water quality sensors being used (Casper et al, ; Mancini et al, ), as well as sensors for tracking and analysing simulated pollutants in freshwater environments (Powers et al, ). Not only do USVs provide the potential for collating bathymetry and water properties but also the surrounding terrestrial environment such as bank morphology and vegetation.…”
Section: Future Directionsmentioning
confidence: 99%